2012
DOI: 10.4028/www.scientific.net/kem.517.617
|View full text |Cite
|
Sign up to set email alerts
|

Characterization Physics, Chemistry and Mineralogy of Waste from Kaolin and their Potential Pozzolanic to Alkali Activation

Abstract: The University Federal of Paraíba has developed various researches to explore the potential for recycling of industrial waste of Paraíba. Among them, the potential of use in the waste generated by processing of kaolin, which is one of the activities of great economic importance to the State of Paraíba and municipalities producers, because it causes a great environmental impact due to lack of an established recycling process. The kaolin processing generates large amounts of waste, one of fractions, a sandy (cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…The main geopolymers precursors used are fly ash and blast furnace slag but also metakaolin. However, other materials such as kaolin waste, red brick waste and weathered soils have not been systematically investigated with regard to development of matrices geopolymerics [10][11][12], possibly because such precursors often contain much lower amounts of aluminium and very high amounts of iron oxide when compared to the main precursors. This paper aims to access the potential use of iron rich sources as precursors for alkaline activation.…”
Section: Introductionmentioning
confidence: 99%
“…The main geopolymers precursors used are fly ash and blast furnace slag but also metakaolin. However, other materials such as kaolin waste, red brick waste and weathered soils have not been systematically investigated with regard to development of matrices geopolymerics [10][11][12], possibly because such precursors often contain much lower amounts of aluminium and very high amounts of iron oxide when compared to the main precursors. This paper aims to access the potential use of iron rich sources as precursors for alkaline activation.…”
Section: Introductionmentioning
confidence: 99%
“…A previous paper of this project [11], looking at the performance of the waste in AAC mortar, showed that the increase of the water demand was the main reason for the reduction in the compressive strength of the test mortars using mica and china clay sand. Other authors have looked at the kaolin waste from Brazil with a focus on altering the leftover kaolinite to metakaolin to use it as binder [12][13][14]. However, that cannot apply to the waste of the UK china clay production, as it does not contain high amounts of left-over kaolinite as present in the waste from Brazil.…”
Section: Introductionmentioning
confidence: 99%